Erythrocytosis associated with hemoglobin Rainier: oxygen equilibria and marrow regulation - Adamson, John W. (1969)
Hemoglobin Rainier (β(145) tyrosine→histidine) is an abnormal hemoglobin associated with increased oxygen affinity, decreased heme-heme interaction, presence of a Bohr effect, and erythrocytosis, but without obvious clinical sequelae. Regulation of erythropoiesis was studied in affected members of families having either hemoglobin Rainier or Yakima, abnormal hemoglobins associated with erythrocytosis. Apart from the elevated but stable hemoglobin concentration and red cell mass, parameters of red cell production in the subjects were normal. Initially normal values of erythropoietin excretion were increased by phlebotomy indicating a significant hypoxic stress at an otherwise normal hematocrit. This stress led to increased reticulocyte production and an eventual return to the prephlebotomy hematocrit. The erythrocytosis in carriers of hemoglobins Rainer and Yakima appears to be secondary to the increased oxygen affinity and this, with the response to phlebotomy, is consistent with the postulate that the renal sensor tissue regulating erythropoietin production is primarily influenced by the oxygen tensions of venous rather than arterial blood.